Silica surface modification using cellulose as a renewable organosilane derived from coconut coir fiber for carbon capture - Hendrix Abdul Ajiz; Rafly Putra Ardiansyah; Mikael Sri Kurnia Raditya Dwiatmaka; Heru Setyawan; Tantular Nurtono; Widiyastuti Widiyastuti (Results in Engineering)
The properties of silica surface modification for carbon capture were studied, utilizing cellulose-amine as a modification agent derived from dissolved coconut coir fiber. To form bonds with NH2 functional groups through amination processes, cellulosic biomass waste is utilized, which is analogous to replacing alkoxy ligands. The dual-function mixture reagents dimethyl sulfoxide (DMSO) and ammonium hydroxide (NH4OH) were employed in the same system as the amine sources and solvents. Waterglass is used as a source of silica, and the modified particles are formed using a one-step consecutive sol-gel spray drying process used in a direct condensation route. Changes in the concentration of sodium lauryl sulfate (SLS) were examined to determine how they affected the essential parameters of the particles. The template is removed during particle formation without further physical or chemical processing. The particle morphology changed from donut-shaped to spherical after SLS application, as evidenced by the increase in SLS concentration. This also shows that the increase in the particle surface area is directly influenced by the increase in the formation of new pore structures with increasing SLS concentration. Through this mechanism, it is possible to extend the pore size distribution to the meso-macropore regime and initiate the formation of new mesopores. This has a direct impact on the capacity to absorb CO2 gas by increasing the cellulose-amine mass fraction that can be grafted to as high as 32.35 %wt. At an operating pressure of 6 bar, a maximum CO2 gas adsorption capacity of 5.32 mmol/g silica was attained by adding SLS 3 CMC to the silica particles. This value is 2.3 times higher than that obtained when using an aminosilane-based modification agent.